Developing multi-professional teamwork for integrated children's services : research, policy and practice - Anning, Angela; Cotrell, David; Frost, Nick; Green, Josephine; Robinson, Mark (Maidenhead, England : Open University Press, 2006)
Multiprofessional practice in the delivery of services is a central government imperative in the UK and other countries. This book offers a practical resource to professionals charged with conceptualising, planning, implementing and evaluating multiprofessional practice in children's services.
Includes bibliographical references and index
EDU
Keywords: Children -- Services for; Social service -- Teamwork